Sanitation Policy in Community-Based Tourism in East Java and Western Australia: A Comparative Analysis - Achmad Room Fitrianto; Asif Iqbal Siddiqui Siddiqui; Ajeng Tita Nawangsari; Nadine Elizabeth GIBBONS; Hapsari Wiji Utami; Iftekhar Ahmed Robin (Journal Public Policy, 2026)
This study examines how sanitation, cultural sensitivity, and tourism policy intersect within community-based tourism (CBT) in East Java, Indonesia, and Western Australia. At its heart, the research seeks practical ways to improve sanitation infrastructure while honoring local cultures and safeguarding the environment—an effort that contributes to ongoing conversations about building truly sustainable tourism. Using a qualitative approach, the study looks closely at public policies, challenges on the ground, and best practices that shape sanitation in CBT settings. Case studies from East Java and Western Australia provide a comparative lens, highlighting both the shared struggles and unique solutions emerging from different contexts. Data were gathered through policy documents, interviews with decision-makers, and direct field observations to capture both structural frameworks and lived experiences. The findings reveal that in Indonesia, efforts to integrate traditional knowledge with modern sanitation practices show promise, but issues of access and long-term maintenance remain pressing. In contrast, Australia demonstrates how consistent attention to hygiene, accessibility, and sustainability can set a strong standard for CBT sanitation. The study underscores that effective sanitation is never the task of a single actor—it depends on collaboration between governments, private partners, and local communities. Lessons from both contexts highlight the value of cross-cultural exchange, policy alignment, and technology in reducing gaps in infrastructure and service delivery. Ultimately, fostering inclusive and sustainable sanitation in CBT requires more than facilities: it calls for policy reforms rooted in cultural respect, investment in green technologies, and the empowerment of communities to lead change. Future research should continue to explore creative solutions that keep sanitation excellence at the center of community-based tourism, ensuring that local well-being and visitor experience advance hand in hand.